PREVALÊNCIA DE SOBREPESO E OBESIDADE EM IDOSOS DA ÁREA RURAL DE IJUÍ, RS - Beier, Liege L.; Rost, Débora; Machado, Luciele d. L.; Bellé, Tânia R. L.; Battisti, Iara D. E.; Schweigert, Ingrid D.; Dallepiane, Loiva B. (Salão do Conhecimento, 2013)
Resumo